Effective Nation Characters Leaders in Connection with Inclusive Design for Preparing The Visionary and Effective of Youth Leaders for Urban Society - Nuah Perdamenta Tarigan (Humaniora, 2014)
While we are looking for a leadership in Jakarta Municipal City from time to time, it is already worsening and not look good for many people, the author is very keen to conduct a research, starting from 2012 up to 2013. There are many degradation already appear in Jakarta in these years, especially for the disappearance of humility, urban genuine life vanish and social alienation, more specific for Jakarta Youth People who will be receiving the next turn of leadership position for Indonesia development and city of Jakarta and its surrounding areas. Before this is too late, the author make a small steps for the development and to transform this situation with the approach of Emphatic Leadership and Management related to CRPD (Convention on The Rights for People with Disability) to enrich and develop the existence of the Youth and the future generation of Indonesia. The approach of this research based on various literatures and journals which are relevant to Community Development, Leadership, Social Entrepreneurship and Management with the depth approach with.